Fractional exhaled nitric oxide (FeNO) and respiratory symptoms in junior high school students in Penang, Malaysia: the role of household exposure - Norback, Dan; Hashim, Jamal Hisham; Hashim, Zailina; Wieslander, Gunilla (Taylor and Francis Ltd., 2024)
We studied associations between fractional exhaled nitric oxide (FeNO), health and household exposure among school children (N = 348) in Penang, Malaysia. Multiple logistic regression and linear mixed models were applied. Overall, 46.0 had elevated FeNO (>20 ppb) and 10.6 diagnosed asthma. Male gender (p = 0.002), parental asthma or allergy (p = 0.047), cat allergy (p = 0.009) and seafood allergy (p < 0.001), diagnosed asthma (p = 0.001), wheeze (p = 0.001), ocular symptoms (p = 0.001), rhinitis (p = 0.002) and respiratory infections (p = 0.004) were all associated with FeNO. Students exposed to ETS had lower FeNO (p = 0.05). Dampness and mould was associated with wheeze (p = 0.038), especially in wooden homes (interaction p = 0.042) and among students with elevated FeNO (interaction p = 0.024). Cat keeping increased rhinitis (p = 0.041) and respiratory infections (p = 0.008) and modified the dampness associations. In conclusion, FeNO can be associated with ocular and respiratory symptoms. Elevated FeNO, cat keeping and a wooden house can enhance the risk of wheeze when exposed to dampness and mould.